A hybrid fuzzy methodology to evaluate customer satisfaction in a public transportation system for Istanbul - Bilisik, Ozge Nalan; Erdogan, Melike; Kaya, Ihsan; Baracli, Hayri (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
Service quality (SERVQUAL) is one of the most important factors that increase the usage of public transportation. SERVQUAL improvements can solve many problems such as traffic congestion, air and noise pollution, and energy consumption in any public transportation system (PTS). In this paper, a hybrid fuzzy approach consisting of SERVQUAL, the Delphi method, fuzzy analytic hierarchy process (AHP) and fuzzy technique for order preference by similarity to ideal solution (TOPSIS) methodologies for the evaluation of SERVQUAL of PTS is presented. The SERVQUAL method is used for classifying the public transportation SERVQUAL evaluation criteria, the Delphi method is used to obtain the evaluations of experts, fuzzy AHP is used to determine the weights of the criteria and fuzzy TOPSIS is used to rank the alternatives. A new linguistic scale is taken into consideration while converting the linguistic evaluations of survey respondents to fuzzy numbers. The proposed approach is applied for the PTS in Istanbul, and the public transportation company that provides the highest customer satisfaction is determined. With this aim, four alternative companies named Istanbul Electric Tramway and Tunnel (IETT), Metrobus, Private Public Transportation Buses and Otobus Inc. are evaluated.
Keywords: customer satisfaction; the fuzzy set theory; multi-criteria decision-making; public transportation; SERVQUAL; Delphi method; AHP; TOPSIS; ANALYTIC HIERARCHY PROCESS; SERVICE QUALITY; DECISION-MAKING; PERFORMANCE; PASSENGERS; USERS; CAR; Business & Economics